IMPLEMENTATION OF BLENDED LEARNING TO INCREASE THE COMPETENCE OF NON-FORMAL EDUCATION UNDERGRADUATE STUDENTS IN THE SOCIOLOGY ANTHROPOLOGY COURSE - Saroinsong, Djony Max; Takaendengan, Wilson (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2022)
This study aims to improve the competence and cognitive learning outcomes of PLS students in the anthropological sociology course through the implementation of blended learning. This research is a class action research (classroom action research) model by Kemmis & McTaggart, which took place in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were ten students of the non-formal education study program at the State University of Manado. Data collection techniques are questionnaire techniques and test techniques. The research data were obtained using communication competency assessment instruments, collaboration competency assessment instruments, and pretest-posttest questions. The data analysis technique used descriptive qualitative data analysis techniques. The results of data analysis showed (1) the communication competence of students in the first cycle was in the less competent category, while in the second cycle they were very competent, (2) the collaboration competence of students in the first cycle was in the less competent category, while in the second cycle they were very competent, (3) students' cognitive learning outcomes showed achievement of 60% in the first cycle, then increased by 40% so that it became 100% in the second cycle. Based on the results of data analysis, we can conclude that the implementation of blended learning can improve the competence and cognitive learning outcomes of PLS students in the sociology of education anthropology course.